Computerized Silent Reading Rate and Strategy Instruction for Fourth Graders at Risk in Silent Reading Rate - Niedo, Jasmin (2013)
Fourth graders whose silent word reading and/or sentence reading rate was, on average, two-thirds standard deviation below their oral reading of real and pseudowords and reading comprehension accuracy were randomly assigned to treatment (n=7) or wait-listed (n=7) control groups. Following nine sessions combining computerized rapid accelerated-reading program (RAP), which individually tailors rate of written text presentation to comprehension criterion (80%), and self-regulated strategies for attending and engaging, the treated group significantly outperformed the wait-listed group before treatment on (a) a grade-normed, silent sentence reading rate task requiring lexical- and syntactic level processing to decide which of three sentences makes sense; and (b) RAP presentation rates yoked to comprehension accuracy level. Each group improved significantly on these same outcomes from before to after instruction. Attention ratings and working memory for written words predicted post-treatment accuracy, which correlated significantly with the silent sentence reading rate score. Implications are discussed for (a) preventing silent reading disabilities during the transition to increasing emphasis on silent reading, (b) evidence-based approaches for making accommodation of extra time on timed tests requiring silent reading, and (c) combining computerized instruction with strategies for self-regulation during silent reading.